Sistem Pakar Diagnosa Penyakit Glaukoma dengan Metode Certainty Factor Berbasis Website - Muhammad Satria; Muhammad Cordiaz (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Eyes are a very important sense tool for humans. Like other sense organs, the eye has a very important function, namely as a sense of sight. The eyes are very sensitive because the eyes are directly dealing with bacteria, infection or dust when we do activities. The hospital handles various complaints about diseases of the human eye, one of which is glaucoma. This is a problem for the Eye Hospital. For this reason, a research entitled "Expert System Diagnosing Glaucoma Eye Disease Using Website-based Certainty Factor Methods was appointed". The research aims to create a computer-based system, then with the implementation of the system, the results of the diagnosis obtained will really be able to replace the role of the doctor if he is not in the hospital. It can be said that by testing the system based on the selected symptoms based on the disease experienced by the patient, it will provide a definite answer to the results of the diagnosis.